The Role of Quality Enhancement Cell in Relation to Culture of Quality and Students’ Academic Performance - Abid Ahmad; Mansoor Ullah; Yasir Arafat; Syed Fahad Ali Shah; Imran Khan (Indus Journal of Social Sciences, 2025)
This paper seeks to understand the impact of culture of quality (COQ) on students’ academic performance and examines the moderating influence of QECs at a university in a private sector. The target population is university student who are studying various undergraduate, and postgraduate courses. A total of 307 valid responses are used for data analysis using regression analysis and PROCESS in SPSS. Results showed significant positive effect of COQ on SAP (β=0.45, p<0.001). The moderation analysis indicates a significant moderating effect of QEC. The positive interaction term between COQ and QEC implies that, the more active QEC gets, the effect of COQ enhances SAP. This implies that that students in the university with a better academic performance perform better when there is a stronger culture of quality in the university. The findings of the study enlarge the theoretical knowledge of quality culture and its effect on academic performance in the higher education. This research demonstrates how COQ has positive effect on Students’ Academic Performance (SAP) and how Quality Enhancement Cell (QEC) as the moderating role on it increases the Education outcome. The results give university administrators and policymakers an idea about how a strong culture of quality can serve as a lever to improve student outcomes.